Removal of Lead and Chromium from Synthetic Wastewater Using Vetiveria zizanioides. Issue 4 (5th September 2014) - Singh, Veralika; Thakur, Lokendra; Mondal, Prasenjit
Abstract The present study deals with the removal of Pb and Cr from synthetic wastewater using Vetiveria zizanioides in a batch scale floating platform unit. The effect of pH, initial concentration of metals, and time on the removal of Pb and Cr has been studied. Vetiveria zizanioides has shown optimum growth at a pH 6–9 and good removal conditions for 5–20 mg/L Pb and Cr. The described process showed good uptake ability for both Pb and Cr, ranging from 80 to 94% for Pb and about 77–78% for Cr, respectively. The uptake of Cr is found to be faster than the Pb uptake process. The removal of Pb has shown an inductive effect whereas Cr removal is found to be non‐inductive. Most of Cr is found to be stored in the stem (28.3 g/kg) of the plant whereas most of Pb is found to be stored in the roots (57.015 g/kg). The performance of the present process seems to be more efficient compared with other phytoremediation methods.